Etfect of biostimulants on the growth and biomass of secondary nursery seedlings of cardamom - NAIDU, B A VADIRAJ, K V V RAMARAO, R (Journal of Spices and Aromatic Crops, 1992)
A nursery experiment was undertaken at the Indian Cardamom Research Institute, Myladumpara to understand the effectofbios tim ulants on the growth and biomass of secondary nursery cardamom s<ledlings. Five biostimulants at different concentrations were sprayed at 30- day intervals for a period of 120 days. The results indicated that biostimulants such as vipul (a tricontanol- containing commercial product), Ergostim (N-acetyl thiazolidne-4-carboxylic acid & folic acid - containing commercial product), pure folic acid, low levels ofsimazine and 2,4-D significantly increased the growth and dry matter production. The results suggest, that application ofbiostimulants not only reduces the nursery period but also helps in getting vigorous seedlings for better establishment in the field.